2010
DOI: 10.1016/j.medengphy.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of electromyography (EMG), mechanomyography (MMG), sonomyography (SMG) and torque output during ramp and step isometric contractions

Abstract: In this study we simultaneously collected ultrasound images, EMG, MMG from the rectus femoris (RF) muscle and torque signal from the leg extensor muscle group of nine male subjects (mean±SD, age=30.7±.4.9 years; body weight=67.0±8.4kg; height=170.4±6.9cm) during step, ramp increasing, and decreasing at three different rates (50%, 25% and 17% MVC/s). The muscle architectural parameters extracted from ultrasound imaging, which reflect muscle contractions, were defined as sonomyography (SMG) in this study. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 92 publications
(126 reference statements)
4
67
0
Order By: Relevance
“…In both studies, the CSA values showed an initial small increase followed by a curvilinear decrease with the increase of torque. The findings on CSA in the present study are also in accordance with our previous study [10], which measured isometric ramp contraction but the CSA values at separate contraction levels were calculated manually. Comparing the relationship curves of both studies, the findings of present study demonstrated more information: 1) the initial increase of CSA can not be observed in previous study because it occurred below the first contraction level; and 2) the reliability of the polynomial regression was improved since there were much more sample points in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In both studies, the CSA values showed an initial small increase followed by a curvilinear decrease with the increase of torque. The findings on CSA in the present study are also in accordance with our previous study [10], which measured isometric ramp contraction but the CSA values at separate contraction levels were calculated manually. Comparing the relationship curves of both studies, the findings of present study demonstrated more information: 1) the initial increase of CSA can not be observed in previous study because it occurred below the first contraction level; and 2) the reliability of the polynomial regression was improved since there were much more sample points in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, data from the literature indicate that EMG activity recorded during submaximal isometric contractions, performed at a similar rate to that of this protocol (20% MVC/s), does not differ significantly from EMG signals acquired during step contractions. 33,34 This suggests that direct EMG comparisons can be done between both protocols. 35 Joint Motion.…”
Section: Methodologicalmentioning
confidence: 99%
“…Other authors have focused on the role of ADL in the upper limb (5,14,15). The lower limb is also widely studied, mainly due to its relevance in human gait (16,17).…”
Section: Disscusionmentioning
confidence: 99%